Hazard Analysis Critical Control Points (HACCP) – Principle 3: Establish Critical Limits and Principle 4: Monitoring Critical Control Points (CCPs) - Ronald H. Schmidt; Debby L. Newslow (EDIS)
FSHN07-05, a 7-page fact sheet by Ronald H. Schmidt and Debby Newslow, takes readers through the process of establishing Critical Limits and monitoring Critical Control Points to ensure food safety in a HACCP system. Published by the UF Department of Food Science and Human Nutrition, July 2007.